Prevention of Gender-Based Violence in Election Supervisory Environments: Problems, Challenges, and Strategies - Saepuddin, Saepuddin; Kusuma, Rizky Dwi (Kybernology : Journal of Government Studies, 2024)
Gender-based violence (GBV) is a critical issue that undermines the integrity of elections and the participation of women in democratic processes. This study aims to identify the problems, challenges, and strategies for preventing GBV in the context of election oversight institutions. Using a qualitative research method with a literature review approach, the study reveals that GBV manifests in various forms, including sexual harassment, verbal intimidation, and gender discrimination. Key challenges include entrenched patriarchal norms, the underrepresentation of women in election oversight leadership, and insufficient policies and reporting mechanisms to address the issue. Mitigation strategies emphasize strengthening regulations, implementing gender-sensitive recruitment processes, and providing GBV education to enhance awareness and commitment among stakeholders. These measures aim to create a safe, inclusive, and violence-free work environment, ensuring professional and integrity-driven election monitoring practices.